Water Use and Reallocation Implications for Economic Growth : A Case Study of Rajasthan - Misra, Smita (World Bank, Washington, DC, 2017)
The key objective of the study is to analyze whether Rajasthan can achieve its economic growth targets with its available water resources and current water allocation pattern. In the above context, the study analyses the water use in agriculture, domestic and industrial(including power) sectors of Rajasthan. It identifies the water allocation patterns in different sectors and calculates the water intensity in each of these sectors. It brings out the constraints that the available water may pose towards achieving the economic growth targets of the State and suggests various strategic options and interventions that policy makers may consider to meet the economic growth target.